Rethinking Nonfunctional Software Requirements. - Hahnle, Reiner; Johnsen, Einar Broch (Computer (00189162), 2015)
Realizing the full potential of virtualized computation-the cloud-requires rethinking software development. Deployment decisions, and their validation, can and should be moved up the development chain into the design phase.